German expansionism, imperial liberalism and the United States, 1776-1945 - Guettel, Jens-Uwe (Cambridge University Press, 2012)
This book traces the connections between American westward expansion and German colonialism from the late eighteenth century to the Nazis' campaign for 'living space in the east' during World War II.